Evaluation of the effect of access point density on the safety of primary roads. a case study - Ahmed, Ashar; Islam, Md. Kamrul; Mohd Sadullah, Ahmad Farhan; Gazder, Uneb (Dr D. Pylarinos, 2024)
This paper investigates the nuanced exploration of access point density's influence on accident frequency, specifically focusing on primary roads in Malaysia. The analysis is multifaceted, considering geographic variations, land use patterns, and the density of access points per km. This investigation scrutinizes the direct relationship between the number of access points per km and the corresponding accident frequency. A critical threshold value for access point density is identified, revealing its consequential impact on average accident frequency. The observed direct proportionality between access point density and accident frequency is a pivotal discovery. Moreover, the role of land use parameters emerges as a key determinant in understanding how accident frequency varies with access point density, particularly on specific road types. This establishes eight access points per km as a potential threshold value for ensuring optimal access point density within a road network. In summary, this study provides insights into the intricate dynamics of access point density and its consequential impact on road safety. The identified threshold value and the recognition of the role of land use contribute valuable perspectives for informed decision-making in road network planning and management.